2023
DOI: 10.1002/ctm2.1334
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3–MLKL necroptotic signalling amplifies STING pathway and exacerbates lethal sepsis

Abstract: Backgrounds The stimulator of interferon genes (STING) is an important driver in various inflammatory diseases. Methods and results Here, we have demonstrated that inhibition of RIPK3 and MLKL dampens STING signaling, indicating that necroptosis may be involved in sustaining STING signaling. Furthermore, RIPK3 knockout in HT‐29 cells significantly suppressed STING signaling. Mechanistically, RIPK3 inhibits autophagic flux during STING activation. RIPK3 knockout inhibits STING signaling by intensifying STING au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Since many of the small molecule inhibitors in the necroptotic pathway have resulted in activation of other cell death pathways, some investigators have suggested that targeting necroptosis response and/or interacting pathways, rather than directly targeting the mediators of necroptosis, may be a more fruitful strategy (Vucur et al, 2023 ; Zhang et al, 2023b ). For example, Vucur and colleagues demonstrated that inhibition of NF-кB limited RIPK3-mediated immune responses in a model of liver cancer and prevented cancer progression (Vucur et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since many of the small molecule inhibitors in the necroptotic pathway have resulted in activation of other cell death pathways, some investigators have suggested that targeting necroptosis response and/or interacting pathways, rather than directly targeting the mediators of necroptosis, may be a more fruitful strategy (Vucur et al, 2023 ; Zhang et al, 2023b ). For example, Vucur and colleagues demonstrated that inhibition of NF-кB limited RIPK3-mediated immune responses in a model of liver cancer and prevented cancer progression (Vucur et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vucur and colleagues demonstrated that inhibition of NF-кB limited RIPK3-mediated immune responses in a model of liver cancer and prevented cancer progression (Vucur et al, 2023 ). STING inhibitors have also been suggested as a potential mechanism to target necroptotic signaling in models of sepsis, due to the interactions between these two signaling pathways (Zhang et al, 2023b ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of necroptosis by RIPK3 or MLKL in macrophages is dependent on DNA sensing and is elevated in autoimmune conditions like systemic lupus erythematosus (SLE) [126]. Necroptotic signaling stimulates STING, whereas suppression of RIPK3 inhibits STING by redirecting STING to autophagosomes [127]. In mouse models, STING agonists induce necroptosis in primary macrophages in vitro in a STING and RIPK3dependent pathway linked to production of and IFN and TNF [128].…”
Section: Necroptosis and Cgas-stingmentioning
confidence: 99%